Kinetically controlled self-assembly of DNA oligomers. - Lubrich, D; Green, S; Turberfield, A (2009)
Metastable two-stranded DNA loops can be assembled into extended DNA oligomers by kinetically controlled self-assembly. Along the designed reaction pathway, the sequence of hybridization reactions is controlled by progressively revealing toeholds required to initiate strand-displacement reactions. The product length depends inversely on seed concentration and ranges from a few hundred to several thousand base-pairs.